Comparison of Medical Education and Requirements for Training in the Interventional Neuroradiology in China, Japan and Korea - Lin Bo Zhao; Shigeru Miyachi; Hai Bin Shi; Dae Chul Suh (Neurointervention, 2013)
The interventional neuroradiology (INR, or neurointerventional surgery) became a rapidly emerging specialty since the first Working group in Interventional Neuroradiology (WIN) meeting was held in Santa Barbara in 1980 by 15 pioneers. Although the specialty has been led by neuroradiologists, other specialists of neurosurgery and neurology have become involved. Due to diverse background of the specialties with inadequate requirement of education and training, proper level of training standard and quality assurance may be achieved for outcomes of treated patients with neurovascular diseases. In East Asia, there are less inter-relationship of education and training among China, Japan and Korea when compared to the learning opportunities in western countries from the three nations. Therefore, we present the current status and difference of medical education system and compare INR training to improve understanding of INR development in the adjacent countries.